Cementoblastic lineage formation in the cross-talk between stem cells of human exfoliated deciduous teeth and epithelial rests of Malassez cells - Farea, Manal; Husein, Adam; Halim, Ahmad Sukari; Berahim, Zurairah; Abdullah Nurul, Asma; Mokhtar@Makhtar, Khairani Idah; Mokhtar, Kasmawati (Springer Berlin Heidelberg, 2015)
Objectives The purpose of this study was to evaluate the synergistic effect of epithelial rests of Malassez cells (ERM) and transforming growth factor-β1 (TGF-β1) on proliferation, cementogenic and osteogenic differentiation of stem cells derived from human exfoliated deciduous teeth (SHED). Materials and methods SHED were co-cultured with ERM with/without TGF-β1. Then, SHED proliferation, morphological appearance, alkaline phosphatase (ALP) activity, mineralization behaviour and gene/protein expression of cemento/osteoblastic phenotype were evaluated. Results TGF-β1 enhanced SHED proliferation when either cultured alone or co-cultured with ERM. ERM induced the cementoblastic differentiation of SHED which was significantly accelerated when treated with TGF-β1. This activity was demonstrated by high ALP activity, strong mineral deposition and upregulation of cementum/bone-related gene and protein expressions (i.e. ALP, collagen type I, bone sialoprotein, osteocalcin and cementum attachment protein). Conclusions ERM were able to induce SHED differentiation along the cemento/osteoblastic lineage that was triggered in the presence of TGF-β1. Clinical relevance The cemento/osteoblastic differentiation capability of SHED possesses a therapeutic potential in endodontic and periodontal tissue engineering.